Cerebrotendinous xanthomatosis without neurological involvement. (8th April 2021) - Stelten, B. M. L.; Raal, F. J.; Marais, A. D.; Riksen, N. P.; Roeters van Lennep, J. E.; Duell, P.B; van der Graaf, M.; Kluijtmans, L. A. J.; Wevers, R. A.; Verrips, A.
Abstract: Background: Cerebrotendinous xanthomatosis (CTX) is an autosomal recessively inherited inborn error of metabolism. Neurological symptoms are considered to be a clinical hallmark of untreated adult patients. We describe a 'milder CTX phenotype', without neurological involvement. Methods: We performed a retrospective patient file study in 79 genetically confirmed Dutch patients with CTX (55 patients aged ≥ 21 years) to study the clinical heterogeneity of CTX. We studied the frequency of adult patients with CTX without neurological involvement at diagnosis, in our Dutch cohort, and included a family from South Africa and patients from Italy, USA, Chile and Asia from the literature. Results: In total, we describe 19 adult patients with CTX from 16 independent families, without neurological symptoms at diagnosis. A relatively small percentage (21%, n = 4) had a history of cataract. The majority, 84% ( n = 16), presented with tendon xanthomas as the sole or predominant feature. The majority of patients showed increased plasma cholesterol levels. No correlation was found between this 'milder phenotype', the cholestanol levels and the CYP27A1 genotype. In addition, we describe three novel mutations in the CYP27A1 gene. Conclusions: This study shows the clinical heterogeneity of CTX, highlighting the existence of a 'milder phenotype', that is without neurological involvement at diagnosis. Adult patients with CTX may present with tendon xanthomas as the sole or predominant feature, mimicking familial hypercholesterolemia. It is important to realize that the absence of neurological symptoms does not rule out the development of future neurological symptoms. As CTX is a treatable disorder, early diagnosis and initiation of treatment when additional clinical signs occur is therefore essential. Abstract :